A Simple Approach to Truss Deflections - Tsai, Wan-Tswan (Engineering Journal, 1976)
The determination of deflections for a longspan truss has long been considered a troublesome subject by structural engineers. Truss deflection is estimated by considering the truss as a beam. The deflection is composed of two portions. One is the bending deflection, which is determined as for a regular beam with moment of inertia evaluated from chord members. The other portion is the shear deflection, which is evaluated from the deformation of web members. The most remarkable feature of this approach is that no member stresses are required. The deflection is given by the direct calculation of simple formulas which already involve the properties of material and geometry.